Forecasting the usage of ambient media in TV broadcasting in the year 2016 - Lugmayr, Artur; Zheng, H. (International Ambient Media Association (iAMEA), 2012)
Technologies in TV broadcasting are rapidly evolving, as also digital media technologies do. Within the scope of this paper, we discuss the application of ambient media technologies in the domain of broadcasting. Ambient media are media that are embedded throughout the natural environment of the consumer and follow the trend towards a ubiquitous society. The trend towards converging media environments across devices as TV sets, PCs, smart mobile phones, intelligent gadgets, and tablets is unstoppable. Internet, broadcasting networks, and service ecosystems become more and more a single service space, rather than having strict boundaries between each medium. The work discusses the current state of utilizing ambient media, and attempts to envision the potential application scenarios of ambient media in the year 2016 in the wider field of TV broadcasting. The key issue for successfully deploying novel services in the area of TV is the creation of service eco-systems emphasizing consumer experience, social interaction, and interactivity. Our study regards the change of consumers' life-styles and points broadcasters to possibilities how to gradually build up a new broadcasting ecosystem on various levels. To develop the vision of how to apply ambient media in the world of broadcasting, we applied various methods: consumer surveys, technology forecasting, expert interviews, and a thorough literature review. We outline a basic roadmap for the potentials of ambient media in broadcasting in the year 2016. Copyright © (2012) by International Ambient Media Association (iAMEA).